Non-destructive measurement of chlorophyll in tomato leaves using spectral transmittance - Jianfeng, Wang; Dongxian, He; Jinxiu, Song; Haijie, Dou; Weifen, Du (International Journal of Agricultural and Biological Engineering, 2015)
In this study, spectral transmittances were measured in the wavelength range from 300 nm to 1100 nm of tomato leaves with different chlorophyll contents and compositions, and the correlations between the spectral transmittances and the contents of chlorophyll a, chlorophyll b and total chlorophyll were analyzed. With the characteristic wavelengths of 560 nm, 650 nm, 720 nm and the reference wavelength of 940 nm, nine sets of characteristic spectral parameters were obtained. According to the results of correlation analysis and regression model exploration, characteristic spectral parameters of T940/T560, T940/T650 and log (T940/T560) among the nine sets of parameters were highly correlated to the estimated contents of chlorophyll a, chlorophyll b and total chlorophyll of tomato leaves. The relative errors of total chlorophyll and chlorophyll a/b ratio were (5.1±3.7)% and (4.9±4.3)%, respectively. Therefore, the above three characteristic spectral parameters could be applied in the rapid non-destructive estimation of the contents of chlorophyll a, chlorophyll b and total chlorophyll as well as chlorophyll a/b ratio of tomato leaves.Keywords: chlorophyll, characteristic wavelength, characteristic spectral parameter, spectral transmittanceDOI: 10.3965/j.ijabe.20150805.1931Citation: Wang J F, He D X, Song J X, Dou H J, Du W F. Non-destructive measurement of chlorophyll in tomato leaves using spectral transmittance. Int J Agric & Biol Eng, 2015; 8(5): 73－78.